APPLICATION OF INVERSE GAS-CHROMATOGRAPHY TECHNIQUE TO THE STUDY OF PVC-PROBE SYSTEMS - OZDEMIR, E; ILTER, Z; COSKUN, M; CELIK, S (Marcel Dekker Inc, 1993)
In this work, some thermodynamic parameters such as weight fraction activity coefficient (a1/w1)infinity, Flory Huggins interaction parameter X for PVC-probe systems at infinite dilution were calculated by using inverse gas chromatography technique. Both (a1/w1)infinity and x were found to be dependent on the chemical nature of the probes and the temperature.
Keywords: Compatibility; Blends